Bimbingan Kelompok untuk Mengembangkan Minat Belajar Siswa SMP: Studi Kasus di Desa Karya Jadi, Kecamatan Batang Serangan - Alfin Siregar; Annisa Fitri; Rizki Assingkily; Rizky Handayani Nasution; Sinta Amalia (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
Interest in learning is a desire to gain knowledge and experience towards good changes in behavior, attitudes, and the ability to interact with individuals in the community. This study provides an overview of the implementation of group guidance services in developing students' low interest in learning and the obstacles faced in implementing group guidance services in Karya Jadi Village, Batang Serangan District. The purpose of implementing group guidance services is to describe and analyze students who have a low interest in learning and provide understanding in developing student interest in learning in Karya Jadi Village, Batang Serangan District. The method used in this study is a qualitative-descriptive method. Data was obtained through three techniques; interviews, observations, and documentation studies. the results of data analysis can be concluded that interest in learning can be developed through an intense group guidance service effort carried out in a way that provides an understanding of the learning model, learning interest, and talents possessed by each student. Keywords: Group Guidance, Learning Model, Interest in Learning, Talent.